FACTORS CONTRIBUTING TO IRREGULAR MIGRATION: A CASE STUDY OF HUMAN TRAFFICKING AMONG MIGRANT WORKERS IN TTS DISTRICT, NTT (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2023)
This paper discusses the main factors that encourage Migrant Workers from East Nusa Tenggara Province, especially those from South Central of Timor District to migrate irregularly. We conducted this study in 6 migrant workers' villages in TTS in May 2018. It applied mixed-methods, qualitative and quantitative approaches. The study involved about 360 respondents who are retired migrant workers or the families of migrant workers. The study found that approximately 42% of the 360 ??respondents answered that the migrant workers from the six villages did not have a birth certificate. About 67% of the migrant workers had an ID card from their area of ??origin. Surprisingly, approximately 33% of migrant workers from those six villages get their identity cards and migration documents from other provinces in Indonesia. Generally, most of the migrant workers from those villages have low levels of education and skills. As many as 28.3% of respondents answered that their household only holds IDR 100,000 in cash a month. The recruiters understand that rural communities have a low level of cash holdings, so they disrupt the civic virtue of Oko Mama in the Atoni Meto culture. Through the Oko Mama, recruiters give some money to the families, parents, husbands, or wives of migrant workers. That money then becomes a debt for the migrant workers. They should repay the money after working work abroad.
Keywords: human trafficking; recruiters; migrant workers; civil documents; irregular migration